Bacterial communities in the rumen of Holstein heifers differ when fed orchardgrass as pasture vs. hay - Mohammed, Riazuddin; Brink, Geoffrey E.; Stevenson, David M.; Neumann, Anthony P.; Beauchemin, Karen A.; Suen, Garret; Weimer, Paul J. (Frontiers in Microbiology, 2014)
The rich and diverse microbiota of the rumen provides ruminant animals the capacity to utilize highly fibrous feedstuffs as their energy source, but there is surprisingly little information on the composition of the microbiome of ruminants fed all-forage diets, despite the importance of such agricultural production systems worldwide. In three 28-d periods, three ruminally-cannulated Holstein heifers sequentially grazed orchardgrass pasture (OP), then were fed orchardgrass hay (OH), then returned to OP. These heifers displayed greater shifts in ruminal bacterial community composition (determined by automated ribosomal intergenic spacer analysis and by pyrotag sequencing of 16S rRNA genes) than did two other heifers maintained 84 d on the same OP. Phyla Firmicutes and Bacteroidetes dominated all ruminal samples, and quantitative PCR indicated that members of the genus Prevotella averaged 23 % of the 16S rRNA gene copies, well below levels previously reported with cows fed total mixed rations. Differences in bacterial community composition and ruminal volatile fatty acid (VFA) profiles were observed between the OP and OH despite similarities in gross chemical composition. Compared to OP, feeding OH increased the molar proportion of ruminal acetate (P = 0.02) and decreased the proportion of ruminal butyrate (P < 0.01), branched-chain VFA (P < 0.01) and the relative population size of the abundant genus Butyrivibrio (P < 0.001), as determined by pyrotag sequencing. Despite the low numbers of animals examined, the observed changes in VFA profile in the rumens of heifers on OP vs. OH are consistent with the shifts in Butyrivibrio abundance and its known physiology as a butyrate producer that ferments both carbohydrates and proteins.